PLAG1 expression and target genes in the hypothalamo-pituitary system in male mice. (15th December 2018) - Juma, Almas R.; Hall, Nathan E.; Wong, Joanne; Gasperoni, Jemma G.; Watanabe, Yugo; Sahota, Akashdeep; Damdimopoulou, Pauliina E.; Grommen, Sylvia V.H.; De Groef, Bert
Abstract: Knockout of pleomorphic adenoma gene 1 (PLAG1) in mice results in reduced fertility. To investigate whether PLAG1 is involved in reproductive control by the hypothalamo-pituitary system in males, we determined PLAG1 expression sites and compared gene expression between hypothalami and pituitary glands from Plag1 knockout and wildtype animals. Abundant expression of PLAG1 was detected throughout the pituitary gland, including gonadotropes and somatotropes. The hypothalamus also contained a large number of PLAG1-expressing cells. PLAG1 was expressed in some gonadotropin-releasing hormone neurons, but not in kisspeptin neurons. Gene ontology analysis indicated upregulation of cell proliferation in both structures, and of cholesterol biosynthesis in the hypothalamus, but functional confirmation is required. Expression levels of pituitary gonadotropins and gonadotropin-releasing hormone receptor, and of brain gonadotropin-releasing hormone and kisspeptin mRNA were unaffected in knockout mice. We conclude that PLAG1 deficiency does not have a major impact on the reproductive control by the hypothalamo-pituitary system. Highlights: PLAG1 is abundantly expressed in pituitary and hypothalamus of male mice. Plag1 KO upregulates genes involved in cell proliferation in both structures. Plag1 KO upregulates genes involved in cholesterol synthesis in hypothalamus. Plag1 KO does not affect expression of genes involved in reproductive control.